Integrating Camelina Into Organic Pig Production—Impact on Growth Performance of Pigs, Costs, and Returns - Li, Yuzhi Z.; Lazarus, W. F.; Reese, C.; Hilbrands, A. M.; Cox, R. B.; Forcella, F.; Gesch, R. W.; Johnston, L. J. (Frontiers in Sustainable Food Systems, 2021)
The sustainability of organic production and cover crops depends on production costs and the economic value of products. Feed cost, contributing 65–75% of the total production cost, has a significant impact on profitability of organic pig farming. Utilizing grains harvested from cover crops as a feed ingredient for organic pigs can potentially protect the environment and increase the economic value of cover crops. This study was the first to evaluate the viability of integrating winter cover crop, camelina, into organic pig production. Winter camelina was grown organically in single or relay with soybeans to increase the total yield per hectare. Camelina yields in monocrop and in relay-crop fields were 1,394 and 684 kg ha−1, respectively. Although the total yield of camelina and soybean (1,894 kg ha−1) in the relay-crop field was higher than camelina yield in the monocrop field, monocropping camelina is more economical than relay-planting with soybeans due to the difference in production costs. Camelina press-cake was supplemented in diets fed to pigs raised under near-organic standards. Supplementing 10% camelina press-cake in diets reduced feed intake, weight gain, final weight at market, carcass weight, and dressing percent of pigs, but did not affect feed efficiency, belly firmness or pork quality. The viability of integrating camelina into organic pig production depends on marketing organic pigs for $2.4 kg−1 of live weight and marketing camelina oil for $3.59 kg−1 or more if monocropping.